Electrochemical Strategy for High‐Resolution Nanostructures in Laser‐Heat‐Mode Resist Toward Next Generation Diffractive Optical Elements. Issue 17 (23rd March 2022) - Wang, Zhengwei; Chen, Guodong; Wen, Ming; Hu, Xutao; Liu, Xing; Wei, Jingsong; Wu, Qingsheng; Fu, YongQing
Abstract: For achieving high‐resolution nanostructures for next‐generation diffractive optical elements (DOEs) using an environmentally friendly process, an electrochemical development strategy is proposed and developed using AgInSbTe‐based laser heat‐mode resist (AIST‐LHR). Based on the electrical resistivity difference of amorphous and crystalline phases for this resist, an etching selectivity ratio of ≈30:1 (i.e., the etch ratio between the amorphous and crystalline ones) is achieved through the oxidation of Fe 3+ ions with the assisted pitting activation etching using Cl − ions in an acid medium. Nanostructures with a minimum feature size down to 41 nm are successfully generated, including grating patterns, meta‐surface optical structures, gears, and English characters. Using a post‐plasma etching process, the nanostructures are successfully transferred from the AIST‐HLR onto silica substrate, and X‐ray grating patterns with a line space of 80 nm are created as a demonstration for its potential applications in DOEs. Abstract : Based on AgInSbTe laser heat‐mode resist, an environmentally friendly and homogeneous electrochemical strategy is explored for high throughput lithography of high‐resolution diffractive optical elements.